Microstrip patch antennas for various applications: a review - Md. Sohel Rana; Sifat Hossain; Shuvashis Biswas Rana; Md. Mostafizur Rahman (Institute of Advanced Engineering and Science, 2023)
This paper aims to review microstrip antennas for various applications. The design of microstrip patch antennas is a new research field developed for use in 5th generation communication applications. An antenna is a collection of multiple devices connected together that function as a single antenna to send or receive radio waves. Antennas can be of different shapes and sizes. The microstrip patch is an antenna pattern that is light in weight, low profile, and focuses on producing results. In the future, microstrip patch antennas may be used for some 6G communication systems applications. In addition, 6G communication applications can be created on other devices, including biomedical, autonomous vehicles, vehicle-to-vehicle (V2V) communication, internet of things (IoT), machine learning, Artificial Neural Network Algorithms, radar, and wireless communication. In the past, the multiple input, multiple output (MIMO) pattern was a standard geometry used in 4G wireless applications. This paper discusses the geometric structures of antennas, various analysis methods for antenna characteristics, antenna dimensions, and many different types of antennas. Also, it will discuss the previous papers' substrate materials, loss tangent, thickness, return loss, bandwidth, voltage-standing-wave-ratio (VSWR), gain, and directivity.